INCIDENCE OF ERYTHROCYTE GLUCOSE-6-PHOSPHATE- DEHYDROGENASE DEFICIENCY - Sh. Rahbar; M. Mir Ahmadian; P. Bahadory; F. Berelian (Iranian Journal of Public Health, 1974)
In a survey carried out to establish the incidence of erythrocyte glucose 6-phosphate-dehydrogenase deficiency, 738 professional blood donors of Tehran were examined.